Adjectival semantics and the legal domain: A study for ontology improvement - Bertoldi, Anderson; De Oliveira Chishman, Rove Luiza; Da Rosa Alves, Isa Mara [UNESP] (My University, 2007)
This paper carries out a descriptive study on Portuguese adjectives. Our aim is to describe the semantics of the legal domain adjectives in order to construct an ontology which may improve Information Retrieval Systems. For this, we present an approach based on valency and semantic relations. The ontology proposed here is a first step aiming to build a legal ontology based on top-level concepts. © AEPIA.
Keywords: Adjectival semantics; Information retrieval; Ontologies